Uniaxial tearing properties and the tearing residual strength models of PTFE coated fabric. (October 2021) - Sun, Xiaoying; He, Rijin; Wu, Yue; Wang, Tengfei
Abstract: This study presents an experimental and analytical investigation on central crack tearing properties of PTFE coated fabric. Firstly, tearing tests under uniaxial tension load were carried out to investigate the influence of crack length and crack orientation on tearing properties of PTFE coated fabric. Tear failure process was carefully recorded and two types of failure modes can be characterized, i.e. progressive failure and brutal failure. The effect of initial crack length and orientation on tearing residual strength (TRS) can be attributed to the numbers of the cut yarns, which can be represented by the equivalent crack length. Secondly, the available TRS models are summarized and discussed in detail. It is found that these models can be classified into two types, i.e. fracture-mechanic-based models and stress-field-based models. By comparing the prediction results with test data, these models present to be only valid for small crack conditions, and the stress-field-based model shows better accuracy.